2011
DOI: 10.1021/nn103493g
|View full text |Cite
|
Sign up to set email alerts
|

Raman 2D-Band Splitting in Graphene: Theory and Experiment

Abstract: We present a systematic experimental and theoretical study of the two-phonon (2D) Raman scattering in graphene under uniaxial tension. The external perturbation unveils that the 2D mode excited with 785 nm has a complex line-shape mainly due to the contribution of two distinct double resonance scattering processes (inner and outer) in the Raman signal. The splitting depends on the direction of the applied strain and the polarization of the incident light. The results give new insight into the nature of the 2D … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
277
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 294 publications
(315 citation statements)
references
References 46 publications
25
277
2
2
Order By: Relevance
“…11 The shift rates of −49.4 and −57.4 cm −1 /%, calculated from first principles, overestimate the experimental values by more than 20% (in absolute value). In another paper, the pairs of shift rates −44.1 and −63.1 cm −1 /% (near-A-strain) and −26.0 and −67.8 cm −1 /% (near-Z-strain), measured at E L = 2.41 eV, have been reported.…”
Section: B Dependence Of the Raman Shift Of The 2d Subbands On ǫmentioning
confidence: 74%
See 4 more Smart Citations
“…11 The shift rates of −49.4 and −57.4 cm −1 /%, calculated from first principles, overestimate the experimental values by more than 20% (in absolute value). In another paper, the pairs of shift rates −44.1 and −63.1 cm −1 /% (near-A-strain) and −26.0 and −67.8 cm −1 /% (near-Z-strain), measured at E L = 2.41 eV, have been reported.…”
Section: B Dependence Of the Raman Shift Of The 2d Subbands On ǫmentioning
confidence: 74%
“…Some authors have concluded that the contributions from these processes are comparable, 11,20 while others have found that the contribution from "outer" processes is negligible compared to that from "inner" ones. 12,21 It has also been argued that the phonon wavevector for a seemingly "outer" process can be transformed by a reciprocal lattice vector to a phonon wavevector for an equivalent "inner" process, "thereby dismissing the notion of inner and outer processes".…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations